Goat Livestock Production Planning Using The Goal Programming Method (Case Study: Living Lab Glugur Rimbun, Sampecita Village, Kutalimbaru District) - Dian Yulis Wulandari; Ismaraidha; Hardiansyah Putra; Shalshabila Putri (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study was conducted to predict the planning of PE goat livestock production in the Al Amin Science and Industrial Park (Living Lab) Area, Glugur Rimbun, Sampecita Village, Kutalimbaru District, Deli Serdang Regency. The method used to predict livestock production planning using Sensitivity Analysis with the Goal Programming Method. The data used is data from Tharaya Farm which has the same management concept as PE goat livestock in the Al Amin Science and Industrial Park (Living Lab) Area, Glugur Rimbun, Sampecita Village, Kutalimbaru District, Deli Serdang Regency later. In this study, the research variables are processed products from goat livestock in the form of goat milk and goat meat. Product A (Goat Milk) requires 30 hours of processing time and product B (Goat Meat) for 20 hours with profits of Rp 400,000 and Rp 800,000, respectively. The results of the study indicate that the profit target can be increased by goat farmers by Rp 1,400,000, - by maximizing the production of at least 2 products for each variable.